People’s willingness to accept overdetection in cancer screening: population survey - Van Den Bruel, A; Jones, C; Yang, Y; Oke, J; Hewitson, P (BMJ Publishing Group, 2015)
To describe the level of overdetection people would find acceptable in screening for breast, prostate, and bowel cancer and whether acceptability is influenced by the magnitude of the benefit from screening and the cancer specific harms from overdetection.Online survey. Women were presented with scenarios on breast and bowel cancer, men with scenarios on prostate and bowel cancer. For each particular cancer, we presented epidemiological information and described the treatment and its consequences. Secondly, we presented two different scenarios of benefit: one indicating a 10% reduction in cancer specific mortality and the second indicating a 50% reduction.Online survey of the population in the United Kingdom.Respondents were part of an existing panel of people who volunteer for online research and were invited by email or online marketing. We recruited 1000 respondents, representative for age and sex for the UK population.Number of cases of overdetection people were willing to accept, ranging from 0-1000 (complete screened population) for each cancer modality and each scenario of benefit.There was large variability between respondents in the level of overdetection they would find acceptable, with medians ranging from 113 to 313 cases of overdetection per 1000 people screened. Across all scenarios, 4-7% of respondents indicated they would accept no overdetection at all compared with 7-14% who thought that it would be acceptable for the entire screened population to be overdetected. Acceptability in screening for bowel cancer was significantly lower than for breast and prostate cancer. People aged 50 or over accepted significantly less overdetection, whereas people with higher education levels accepted more; 29% of respondents had heard of overdetection before.Acceptability of overdetection in cancer screening is variable. Invitations for screening should include clear information on the likelihood and consequences of overdetection to allow people to make an informed choice.